PERANCANGAN SISTEM CERDAS CHATBOT ADMIN TOKO ONLINE DENGAN ALGORITMA LEVESHTEIN DISTANCE - Ibrahim, Mulyana; Imam Agung, Achmad; Sucipto, Hadi (Inovate, 2020)
The progress of technology has become faster every year, this progress has impact so many aspec of humanslife. One of the aspec that change so much in this days is online shopping where the seller sell their producton the internet and the customer buy it from the internet. The phenomenon make the need of cutomer servicebecome more crucial than before. Because of this phenomenon this research try to make the system thatcan change customer service with chatbot. The method that used in this research is a string matching withLevenshtein Distance algorithm. After the string matching has a result, the result that will be manipulatewith natutal language processing so the customer who use the system will feel talk with human rather thanwith the machine. The resault of this research is a system that can make a conversation with humanlanguage. From the test indicating the system can handle a couples user in the same time, and from the testgive a resault that system can understand the word that being inputed.Keyword: Chatbot, Levenshtein Distane(LD), Natural Language Processing(NLP).